What Do University Students Know about Sustainable Development Goals? A Realistic Approach to the Reception of this UN Program Amongst the Youth Population - Zamora-Polo, Francisco; Sánchez-Martín, Jesús; Corrales-Serrano, Mario; Espejo-Antúnez, Luis (Sustainability, 2019)
The Sustainable Development Goals (SDGs) constitute a working agenda for the international community with the aim of ensuring a better world for future generations. In this context, the development of competences related to SDGs is a challenge for Higher Education Institutions. Although there are several studies that address the relationship between SDGs and university teaching, the students’ knowledge about this subject has not been set out yet. In order to evaluate students’ knowledge, a questionnaire was designed, validated, and administered to students from different degrees. Statistical analysis showed a high reliability for the constructs (Smallest Cronbach’s Alfa = 0.859). The results showed interesting insights, either with descriptive analysis or inferential ones. For example, a low knowledge, in a general way, of SDGs was identified in the whole sample; significant differences between the scores obtained in professional and personal implications of SDGs were also detected and several differences arose between Health and Education students, the latter being more professionally involved with SDGs than the rest of the students.